2011
DOI: 10.1037/a0021754
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias modification: Induced interpretive biases affect memory.

Abstract: Previous research has shown that it is possible to experimentally induce interpretive biases using ambiguous scenarios. This study extends past findings by examining the effects of cognitive bias modification for interpretation on subsequent scenario recall. Participants were trained to interpret emotionally ambiguous passages in either a positive or negative direction. Transfer of the training to novel scenarios was tested. After training, participants were also asked to recall details from these novel scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 49 publications
11
60
1
3
Order By: Relevance
“…Under conditions of heightened self-focus, distorted interpretations of ambiguous information transfer to memory (experiment 2, Hertel & El-Messidi, 2006). Third, acquired interpretation biases influence memory for past ambiguous information and memory for subsequently encountered information Tran et al, 2011).…”
Section: Combined Cognitive Bias Hypothesis In Depression 20mentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of heightened self-focus, distorted interpretations of ambiguous information transfer to memory (experiment 2, Hertel & El-Messidi, 2006). Third, acquired interpretation biases influence memory for past ambiguous information and memory for subsequently encountered information Tran et al, 2011).…”
Section: Combined Cognitive Bias Hypothesis In Depression 20mentioning
confidence: 99%
“…No training-group differences emerged in recall of initial scenarios. These results were extended by Tran, Hertel, and Joormann (2011). After a positive or negative interpretation bias training (procedure similar to Mathews & Mackintosh, 2000), ambiguous stories ending with a to-be-completed word fragment were presented to the COMBINED COGNITIVE BIAS HYPOTHESIS IN DEPRESSION 19 participants (encoding phase).…”
Section: Causal Questionsmentioning
confidence: 99%
“…In this respect, cognitive bias ATTENTION,INTERPRETATION,AND MEMORY BIASES 22 modification procedures provide the necessary tools to test causal pathways (see Koster, Fox, & MacLeod, 2009). Noteworthy are studies by Salemink et al (2010) and Tran et al (2011) that have investigated the influence of interpretation on memory bias by inducing negative and positive interpretive biases in nonclinical samples. However, many other links (e.g., how memory bias may guide attention) between biased cognitive processes need future empirical consideration.…”
Section: Attention Interpretation and Memory Biases 18mentioning
confidence: 99%
“…A first study found that participants trained to interpret ambiguous information negatively exhibited improved recall of negative endings of ambiguous scenarios that were presented before the interpretation training, and vice versa for positive information (Salemink, Hertel, & Mackintosh, 2010). In addition, a second training study demonstrated that trained interpretation biases, either positive or negative, can also affect memory for subsequently encountered ambiguous scenarios in a bias congruent manner (Tran, Hertel, & Joormann, 2011). In line with these findings, Hertel and El-Messidi (2006) observed that, under conditions of experimentally heightened self-focused attention, subclinically depressed individuals interpret homographs (e.g., dump, blue) more often as personal and subsequently recall these interpretations to an increased extent.…”
Section: Relations Between Cognitive Biasesmentioning
confidence: 99%